Activation and characterization of a cryptic gene cluster reveals a cyclization cascade for polycyclic tetramate macrolactams. Issue 2 (14th November 2016) - Saha, Subhasish; Zhang, Wenjun; Zhang, Guangtao; Zhu, Yiguang; Chen, Yuchan; Liu, Wei; Yuan, Chengshan; Zhang, Qingbo; Zhang, Haibo; Zhang, Liping; Zhang, Weimin; Zhang, Changsheng
Abstract : We report the activation of a PTM gene cluster in marine-derived Streptomyces pactum, leading to the discovery of six new PTMs, the pactamides A-F. Abstract : Polycyclic tetramate macrolactams (PTMs) are a growing class of natural products and are derived from a hybrid polyketide synthase (PKS)/non-ribosomal peptide synthetase (NRPS) pathway. PTM biosynthetic gene clusters are conserved and widely distributed in bacteria, however, most of them remain silent. Herein we report the activation of a PTM gene cluster in marine-derived Streptomyces pactum SCSIO 02999 by promoter engineering and heterologous expression, leading to the discovery of six new PTMs, pactamides A–F (11–16 ), with potent cytotoxic activity upon several human cancer cell lines. In vivo gene disruption experiments and in vitro biochemical assays reveal a reductive cyclization cascade for polycycle formation, with reactions sequentially generating the 5, 5/5 and 5/5/6 carbocyclic ring systems, catalysed by the phytoene dehydrogenase PtmB2, the oxidoreductase PtmB1, and the alcohol dehydrogenase PtmC, respectively. Furthermore, PtmC was demonstrated as a bifunctional cyclase for catalyzing the formation of the inner five-membered ring in ikarugamycin. This study suggests the possibility of finding more bioactive PTMs by genome mining and discloses a general mechanism for the formation of 5/5/6-type carbocyclic rings in PTMs.